THE RELATIONSHIP OF STRESS LEVEL WITH MENSTRUAL CYCLE IN MIDWIFE AT RSUD DR. SOETOMO DURING THE COVID-19 PANDEMIC - Bambang Purwanto; Atika; Dwi Wulan Suci (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: An interrupted menstrual cycle can indicate reproductive system problems. However, there are several factors that can affect the length of the menstrual cycle such as nutritional status, diet, stress, hormonal drugs, smoking, and sleep quality. The current COVID-19 pandemic has had a major impact, one of which is an increase in stress, especially for health workers who serve COVID-19 problems. This study aims to analyze the relationship between stress levels with the length of the midwife's menstrual cycle during the COVID-19 pandemic. Methods: The type of research that will be used is an observational analytic study using a cross sectional design. The number of samples used were 47 midwives who work in RSUD Dr. Soetomo Surabaya during the COVID-19 pandemic. Bivariate analysis using Spearman tests. Results: There were 63.8% of midwives who had moderate stress levels and 88.2% of midwives with normal menstrual cycle length. The results of the analysis showed that there was no relationship between the midwife's stress level with the length of her menstrual cycle with p=0,660 and p = 0.568. Conclusion: Based on the results of this study, it can be concluded that there is no relationship between stress levels with the length of the menstrual cycle in midwives during the COVID-19 pandemic, so education and information about stress handling mechanisms are needed so that stress does not increase.  Keywords: Stress level, menstrual cycle length, COVID-19 pandemic